Differential subcellular distribution renders HAI-2 a less effective protease inhibitor than HAI-1 in the control of extracellular matriptase proteolytic activity - Yi-Lin Chiu; Yi-Ying Wu; Robert B. Barndt; Yu-Wen Lin; Hou-Ping Sytwo; Amy Cheng; Kacy Yang; Khee-Siang Chan; Jehng-Kang Wang; Michael D. Johnson; Chen-Yong Lin (Genes and Diseases, 2022)
The integral membrane, Kunitz-type serine protease inhibitors HAI-1 and HAI-2, can suppress the proteolytic activity of the type 2 transmembrane serine protease matriptase with high specificity and potency. High levels of extracellular matriptase proteolytic activity have, however, been observed in some neoplastic B-cells with high levels of endogenous HAI-2, indicating that HAI-2 may be an ineffective matriptase inhibitor at the cellular level. The different effectiveness of the HAIs in the control of extracellular matriptase proteolytic activity is examined here. Upon inducing matriptase zymogen activation in the HAI Teton Daudi Burkitt lymphoma cells, which naturally express matriptase with very low levels of HAI-2 and no HAI-1, nascent active matriptase was rapidly inhibited or shed as an enzymatically active enzyme. With increasing HAI-1 expression, cellular matriptase-HAI-1 complex increased, and extracellular active matriptase decreased proportionally. Increasing HAI-2 expression, however, resulted in cellular matriptase-HAI-2 complex levels reaching a plateau, while extracellular active matriptase remained high. In contrast to this differential effect, both HAI-1 and HAI-2, even at very low levels, were shown to promote the expression and cell-surface translocation of endogenous matriptase. The difference in the suppression of extracellular active matriptase by the two closely related serine protease inhibitors could result from the primarily cell surface expression of HAI-1 compared to the mainly intracellular localization of HAI-2. The HAIs, therefore, resemble one another with respect to promoting matriptase expression and surface translocation but differ in their effectiveness in the control of extracellular matriptase enzymatic activity.